2011
DOI: 10.1002/pros.21438
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine induces cell‐cycle arrest and apoptosis in androgen‐dependent and ‐independent prostate cancer cell lines, LNcap‐FGC‐10, DU‐145, and PC3

Abstract: Our results suggest that adenosine induced apoptosis in prostate cancer cells via the mitochondrial pathway and is related to the adenosine receptors. These data might suggest that adenosine could be used as an agent for the treatment of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
41
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 66 publications
(79 reference statements)
9
41
2
Order By: Relevance
“…Panjehpour et al [16] demonstrated that in DU145 prostate cancer cells, the A 2B AR was the highest expressed and the A 3 AR was the lowest expressed (almost undetectable) among the four subtypes of ARs. The results from the present study are different from those of Aghaei et al [14], who reported a different AR expression pattern with the A 3 AR being highly expressed. Fishman et al [17] reported that the A 3 AR agonist IB-MECA at concentrations from 0.01 to 10 μM inhibited growth of PC-3 cells, but the expression profile of four ARs was not examined.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Panjehpour et al [16] demonstrated that in DU145 prostate cancer cells, the A 2B AR was the highest expressed and the A 3 AR was the lowest expressed (almost undetectable) among the four subtypes of ARs. The results from the present study are different from those of Aghaei et al [14], who reported a different AR expression pattern with the A 3 AR being highly expressed. Fishman et al [17] reported that the A 3 AR agonist IB-MECA at concentrations from 0.01 to 10 μM inhibited growth of PC-3 cells, but the expression profile of four ARs was not examined.…”
Section: Discussioncontrasting
confidence: 99%
“…The A 2B AR has been identified as one of several GPCRs expressed at a considerably high level in some cancer tissues including prostate cancer [5]. However, the role of the A 2B AR in prostate cancer has not been systematically investigated and reliably identified [13,14]. This was, at least, in part, because many previous studies utilized adenosine and analogs that acted nonselectively on the ARs [13,15] rather than selective A 2B AR agonists or antagonists or siRNA specific for the A 2B AR.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were shown in these three cell lines when they were treated by adenosine (16). Both groups of agonists were shown to induce apoptosis and promoted G 0 /G 1 cell-cycle arrest through p53, cyclin-dependent kinase 4 (CDK4)/cyclin D1-mediated pathways (15,16). An evaluation of purinergic action in lineage-related cells ranging from androgen-sensitive to castrate-resistant as far as we are aware has not been performed.…”
supporting
confidence: 61%
“…An A 3 agonist was shown to have dose-dependent antiproliferative effects on androgen-sensitive (LNCaP-FGC10) and androgen-independent (DU145 and PC-3) PCa cells (15). Similar effects were shown in these three cell lines when they were treated by adenosine (16). Both groups of agonists were shown to induce apoptosis and promoted G 0 /G 1 cell-cycle arrest through p53, cyclin-dependent kinase 4 (CDK4)/cyclin D1-mediated pathways (15,16).…”
mentioning
confidence: 72%
“…Cell viability was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay as described previously [23,24]. The A-431 cells were seeded at 5 × 10 3 cells/well in 5% CO2 at 37°C in RPMI medium (containing 10% FBS, 100 units⁄ml penicillin and 100 μg ⁄ml streptomycin) in 96-well plates.…”
Section: Cell Viability Assay With Mtt Reductionmentioning
confidence: 99%